Laminate

The laminate with core-sheath composite fibers and a resin film addresses issues of flapping and shape loss in roll blinds and bags, ensuring strength, flexibility, and safety for bathroom use.

JP2025010670APending Publication Date: 2025-01-23KURARAY PLAST CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023112773
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-23

AI Technical Summary

Technical Problem

Conventional membrane materials used for roll blinds and bags face issues such as flapping in the wind, loss of shape, exposure of glass fibers, and visibility of core materials, making them unsuitable for certain applications.

Method used

A laminate comprising a fiber fabric with core-sheath composite fibers and a resin film, where the sheath has a lower melting point than the core, and specific thread counts and thicknesses are used to enhance strength, flexibility, and maintainability.

Benefits of technology

The laminate maintains shape integrity, prevents sagging, and is safe for use in bathrooms without glass fiber exposure, offering excellent flexibility and maintainability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010670000001_ABST
    Figure 2025010670000001_ABST
Patent Text Reader

Abstract

To provide a laminate which is safely usable in a bathroom and the like, is excellent in shape formability, prevents deformation when applied to a bag and the like, has adequate strength / flexibility and is excellent in maintainability.SOLUTION: A laminate has a resin film provided on at least one surface of a fiber fabric, wherein the fiber fabric has large surface density and an adequate weight, sheath-core composite fibers are used, and a sheath part of the sheath-core composite fiber has a melting point lower than that of the core part.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate that can be suitably used for applications such as roller blinds and bags. [Background technology]

[0002] Conventionally, membrane materials made of polyester or other fiber fabrics coated or laminated with thermoplastic resin have been used as materials for roll blinds, bags, etc. (Patent Document 1). Such membrane materials are excellent in both strength and ease of maintenance, but when used as roll blinds, they may flap in the wind and lose their flatness. In addition, when such membrane materials are used for bags, there are problems such as the bag not being able to stand on its own and losing its shape when placed on the floor.

[0003] As a method for improving the flatness of the above-mentioned roll blinds, it is known to use glass cloth as the fabric. This provides appropriate rigidity and dimensional stability, and produces a sheet with good flatness. However, when glass cloth is used as the fabric, glass fibers are exposed at the cut parts, and there is a possibility that the glass fibers may pierce the hands or other parts of the body, making it unsuitable for use in bathrooms, etc.

[0004] In addition, when it comes to bag applications, the use of core material as a reinforcing material in the bag prevents the bag from losing its shape, but the core material is visible in the framework, which can mar the bag's appearance. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 5165468 Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the above background, an object of the present invention is to provide a laminate which can be safely used in a bathroom, etc., has excellent shape-forming properties, is resistant to deformation when used in bags, etc., has appropriate strength and flexibility, and is easy to maintain. [Means for solving the problem]

[0007] As a result of intensive research, the inventors have found that the above-mentioned problems can be solved by a laminate having a resin film on at least one side of a fiber fabric, which is configured so as to reduce voids in the plane of the fiber fabric, and which has an appropriate weight and contains as its constituent fibers 50% by mass or more of core-sheath composite fibers in which the melting point of the sheath is lower than that of the core.

[0008] That is, the object of the present invention is to [1] A laminate comprising at least one fiber fabric and at least one resin film, the resin film being arranged in a state of being adhered to at least one surface of the fiber fabric, the number of warp threads and weft threads of the fiber fabric being 20 threads / inch to 60 threads / inch, the fineness of the warp threads and weft threads being 50 dtex to 950 dtex, the fibers constituting the fiber fabric containing 50 mass% or more of core-sheath composite fibers, the sheath part of the core-sheath composite fibers having a lower melting point than the core part, and the melting point of the sheath part being 100°C to 180°C; [2] The laminate according to [1], wherein 90% by mass or more of the fibers constituting the fiber woven fabric are organic fibers; [3] The laminate according to [1] or [2], wherein the resin film contains a thermoplastic resin; [4] The laminate according to [3], wherein the thermoplastic resin constituting the resin film contains at least one selected from the group consisting of vinyl chloride, vinyl chloride copolymers, ethylene-vinyl acetate copolymers, polyurethane resins, polyester resins, and acrylic resins; or [5] A laminate comprising at least one fiber fabric and at least one resin film, the resin film being arranged in a state of being adhered to at least one surface of the fiber fabric, the fiber fabric having a cover factor calculated by the following formula (I) in the range of 600 to 1900, and a basis weight of the fiber fabric of 250 g / m 2 The fibers constituting the fiber woven fabric contain 50% by mass or more of sheath-core composite fibers, the sheath of the core-sheath composite fibers has a lower melting point than the core, and the melting point of the sheath is 100°C to 180°C. Formula (I): Cover factor = (number of warp yarns × √ warp fineness (dtex)) + (number of weft yarns × √ weft fineness (dtex)); [6] A laminate comprising at least one fiber woven fabric and at least one resin film, the resin film being bonded to at least one surface of the fiber woven fabric, and the fiber woven fabric having a basis weight of 50 g / m 2 ~250g / m 2 a fiber woven fabric having a thickness of 50 μm to 400 μm, fibers constituting the fiber woven fabric containing 50 mass % or more of sheath-core composite fibers, the sheath of the core-sheath composite fibers having a lower melting point than the core, and the melting point of the sheath being 100° C. to 180° C.; [7] A roll curtain comprising the laminate of the above [1] to [6]; This is achieved by: Effect of the Invention

[0009] According to the present invention, it is possible to provide a laminate which can be safely used in a bathroom etc., has excellent shape forming properties, is resistant to deformation when used in a bag etc., has appropriate strength and flexibility, and is easy to maintain. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is a diagram showing an example of a cross section of a laminate of the present invention. [Diagram 2] FIG. 4 is a diagram showing another example of a cross section of the laminate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The laminate of the present invention is a laminate having a resin film provided on at least one side of a fiber woven fabric, the fiber woven fabric is made of a core-sheath composite fiber, and the sheath of the core-sheath composite fiber has a lower melting point than the core. The laminate preferably has a structure of either "resin film / fiber woven fabric / resin film" or "resin film / fiber woven fabric."

[0012] One of the characteristics of the fiber fabric constituting the laminate of the present invention is that it is configured to have small voids in a plane, has a moderate weight, and contains core-sheath composite fibers. Specifically, it has the characteristics specified for the fiber fabric in embodiment 1, 2 or 3 described below. The first embodiment is a laminate comprising at least one fiber fabric and at least one resin film, the resin film being arranged in a state of being adhered to at least one surface of the fiber fabric, the number of warp threads and weft threads of the fiber fabric being 20 threads / inch to 60 threads / inch, respectively, the total fineness of the fibers constituting the warp threads and weft threads being 50 dtex to 950 dtex, the fibers constituting the fiber fabric containing 50 mass% or more of sheath-core composite fibers, the sheath portion of the core-sheath composite fibers having a lower melting point than the core portion, and the melting point of the sheath portion being 100°C to 180°C. A second embodiment is a laminate, the laminate comprising at least one fiber woven fabric and at least one resin film, the resin film being arranged in a state of being adhered to at least one surface of the fiber woven fabric, the cover factor of the fiber woven fabric calculated by the formula (I) being within a range of 600 to 1900, and the basis weight of the fiber woven fabric being 250 g / m 2 The fibers constituting the fiber fabric are a laminate containing 50% by mass or more of sheath-core composite fibers, the sheath of the core-sheath composite fibers having a lower melting point than the core, and the melting point of the sheath is 100°C to 180°C. A third embodiment is a laminate, the laminate comprising at least one fiber woven fabric and at least one resin film, the resin film being arranged in a state of being adhered to at least one surface of the fiber woven fabric, and the fiber woven fabric having a basis weight of 50 g / m2 ~250g / m 2 The fiber woven fabric has a thickness of 50 μm to 400 μm, the fibers constituting the fiber woven fabric contain 50 mass % or more of sheath-core composite fibers, the sheath of the core-sheath composite fibers has a lower melting point than the core, and the melting point of the sheath is 100° C. to 180° C. A laminate having any two of the features of the first, second and third embodiments, and a laminate having all of the features of the first to third embodiments are both suitable aspects of the present invention.

[0013] From the viewpoint of flexibility and light weight, it is preferable that the fibers constituting the fiber fabric, including both the core-sheath composite fibers and other fibers (fibers other than the core-sheath composite fibers), are 90% by mass or more of organic fibers, and it is more preferable that the organic fibers are 100% by mass.

[0014] The fiber woven fabric constituting the laminate of the present invention contains 50% by mass or more, preferably 60% by mass or more, more preferably 75% by mass or more, even more preferably 85% by mass or more, still more preferably 95% by mass or more, and particularly preferably 100% by mass of core-sheath composite fibers among its constituent fibers. If the content of core-sheath composite fibers in the fiber woven fabric is less than 50% by mass, not only will the adhesion between the resin film and the fiber woven fabric decrease, but the flatness of the laminate will be impaired due to the difference in shrinkage between the core-sheath composite fibers and other fibers. Furthermore, when a sheath-core composite fiber is used in combination with other fibers, the sheath-core composite fiber is present in the woven fabric "in twisted yarns," "part of the warp or weft," or "the warp is sheath-core composite fiber and the weft is other fibers, or the warp is other fibers and the weft is sheath-core composite fiber," preferably in the form of "in twisted yarns" or "the warp is sheath-core composite fiber and the weft is other fibers, or the warp is other fibers and the weft is sheath-core composite fiber," and particularly preferably in the form of "the warp is sheath-core composite fiber, the weft is other fibers, or the warp is other fibers and the weft is sheath-core composite fiber." This is because when sheath-core composite fiber and other fibers are mixed with fibers in the same direction, the flatness of the laminate may be impaired due to the difference in shrinkage.

[0015] In the case of a core-sheath composite fiber, the cross section cut perpendicular to the longitudinal direction of the fiber has a sheath-core shape, and the material arranged in the sheath is arranged so as to cover the entire surface of the fiber. There may be one or more cores. When there is one core, the cross section may be concentric or eccentric, and when there are multiple cores, the cross section may be a composite shape such as an islands-in-the-sea type. The cross section may be round, or may have various irregular shapes such as a flat cross section, polygonal, T-shaped, or Y-shaped. The core or sheath may have a hollow portion.

[0016] The sheath of the core-sheath composite fiber contained in the fiber fabric constituting the present invention has a lower melting point than the core. That is, the melting point of the material disposed in the sheath is a temperature lower than the melting point of the material disposed in the core. The sheath melting point (the melting point of the material disposed in the sheath) is 100°C to 180°C, preferably 120°C to 180°C, more preferably 140°C to 180°C, and even more preferably 150°C to 170°C. If the sheath melting point is 100°C or higher, it is possible to suppress the sheath from softening and causing blocking due to storage in a warehouse in summer, and it is also possible to prevent the sheath from softening and causing slippage (heat-resistant creep) between the resin film and the fiber fabric and causing loss of flatness when used outdoors in summer, and if the sheath melting point is 180°C or lower, it is possible to set processing conditions within a range that does not cause deterioration of the resin film. The melting point of the core (the melting point of the material disposed in the core) is preferably at least 10° C. higher than the melting point of the sheath, more preferably at least 20° C. higher, and even more preferably at least 30° C. higher. If this temperature difference is small, the core will soften along with the sheath when preparing the laminate, which may reduce the strength of the fiber fabric and the laminate using it.

[0017] The core-sheath composite fiber used in the present invention preferably contains polyester resin, polyamide resin, acrylic resin, polyvinyl alcohol resin, polyvinyl chloride resin, polyvinylidene fluoride resin, polyurethane resin, polynosic resin, polychral resin, aramid resin, acetate resin, polyolefin resin, or a mixture thereof in both the core and the sheath, and the resin types used in the core and the sheath may be different or the same. Among them, it is preferable that polyamide resin and / or polyester resin is contained, and it is particularly preferable that both the core and the sheath contain polyester resin from the viewpoint of physical properties and chemical properties. As the form of the core-sheath composite fiber, both long fibers and short fibers can be used, but long fibers are preferable from the viewpoint of strength. In addition, recycled polyester can be used as the fiber constituting the core.

[0018] In addition, the fibers other than the core-sheath composite fibers in the fiber fabric (other fibers: for example, normal fibers (single component)) are preferably at least one selected from polyester-based fibers, polyamide-based fibers, acrylic-based fibers, polyvinyl alcohol fibers, polyvinyl chloride-based fibers, polyvinylidene fluoride-based fibers, polyurethane-based fibers, polynosic fibers, polyclar fibers, acetate fibers, aramid fibers, acetate-based fibers, and polyolefin-based fibers, more preferably polyamide-based fibers and / or polyester fibers, and even more preferably polyester fibers.

[0019] In the first embodiment, the fineness of the warp and weft yarns is 50 dtex to 950 dtex, preferably 150 dtex to 850 dtex, more preferably 200 dtex to 750 dtex, and even more preferably 250 dtex to 650 dtex. When the fineness is 50 dtex or more, it is possible to maintain a suitable strength, and even if the laminate is repeatedly unwound and unwound, it is possible to prevent the membrane from sagging and losing its flatness. Also, when the fineness is 950 dtex or less, it is possible to maintain flexibility, to easily incorporate into the device, and to appropriately reduce the weight. Also, it is preferable that the above-mentioned range of fineness is satisfied in each of the embodiments 2 and 3. Note that the fineness here refers to the total fineness when the warp yarn and / or weft yarn is formed by bundling a plurality of fibers.

[0020] The core of the sheath-core composite fiber can be made of dyed resin. By using dyed resin, dyeing and washing processes are unnecessary, reducing water consumption, energy consumption, and CO 2 It reduces emissions, is less likely to discolor, and inhibits color transfer to resin films, etc.

[0021] The weave of the fiber fabric used in this embodiment may be plain weave, twill weave, satin weave, rib weave, basket weave, herringbone twill, or overlapped satin weave, of which plain weave, rib weave, and basket weave are preferred, and plain weave is more preferred. By using this weave, the number of intersections of the yarns increases, resulting in a laminate in which the membrane material is less likely to sag due to repeated unwinding and unwinding.

[0022] In the first embodiment, the number of warp threads and weft threads in the weave of the fiber woven fabric is 20 threads / inch to 60 threads / inch or less, preferably 24 threads / inch or more, more preferably 36 threads / inch or more, for example, 48 threads / inch is a suitable embodiment. When the number of threads is 20 threads / inch or more, an appropriate tensile strength is maintained and dimensional change when hung for a long time can be reduced. When the number of threads is 60 threads / inch or less, flexibility is maintained within an appropriate range and an increase in processing man-hours and weight when incorporated into a device can be suppressed. Also in the second and third embodiments, it is preferable that the number of threads falls within the above range.

[0023] In the second embodiment, the cover factor of the fiber woven fabric calculated from the following formula (I) is 600 to 1900, preferably 1000 to 1900, and in one preferred embodiment, 1300 to 1700. When the cover factor is 600 or more, dimensional change during long-term hanging can be reduced. Also, when the cover factor is 1900 or less, flexibility is maintained within an appropriate range, and an increase in processing steps and weight when incorporating into a device can be suppressed. Formula (I): Cover factor = (number of warp yarns x √ warp fineness (dtex)) + (number of weft yarns x √ weft fineness (dtex)) Also in the first and / or third embodiment, it is preferable that the above-mentioned range of the cover factor is satisfied.

[0024] In the second or third embodiment, the fiber woven fabric has a basis weight of 250 g / m 2 Less than or equal to 200m, preferably 2 / g or less, and more preferably 150m 2 / g or less, more preferably 120m 2 / g or less. 2 When the molecular weight is 1 / g or less, it is possible to suppress an increase in the number of steps required for processing when the polymer is incorporated into an apparatus and a burden on the apparatus due to an increase in the product weight can be suppressed. Also in the first embodiment, it is preferable that the basis weight falls within the above range. In the third embodiment, the fiber woven fabric has a basis weight of 50 g / m 2 More preferably, it is 80 g / m 2 That's all. The weight is 50m 2 When the elastic modulus is 1 / g or more, a suitable strength can be maintained, and even if the laminate is repeatedly unwound and unwound, the film can be prevented from sagging and the flatness can be prevented from being impaired. In the first and / or second embodiment, it is also preferable that the basis weight falls within the above range.

[0025] In the third embodiment, the thickness of the fiber fabric is 50 μm to 400 μm. Here, the thickness refers to the average thickness of three points measured at any three points on the fiber fabric using a dial gauge with a smooth terminal tip. The thickness of the fiber fabric is preferably 100 μm to 300 μm, more preferably 150 μm to 250 μm, and even more preferably 150 μm to 200 μm. When the thickness is 50 μm or more, it is possible to maintain a suitable strength, and even if the laminate is repeatedly unwound and unwound, it is possible to prevent the film from sagging and the flatness from being damaged. Furthermore, when the thickness is 400 μm or less, it is possible to keep the weight within a suitable range, and when used as a roll curtain, the roll diameter when rolled is small, making it possible to miniaturize the device. Moreover, in the first embodiment and / or the second embodiment, it is preferable that the thickness falls within the above range.

[0026] The above-mentioned fiber woven fabric may be subjected to a water-repellent treatment for preventing the infiltration of water due to the capillary phenomenon of the multifilament yarns constituting the woven fabric, a flame-retardant treatment for self-extinguishing properties, an adhesive treatment for improving adhesion to a resin film, etc. Examples of the water-repellent treatment include treatment with a fluorine-based water-repellent agent, a silicone-based water-repellent agent, etc. Examples of the flame retardant treatment include treatments with halogen compounds such as brominated polystyrene and brominated aromatic triazine compounds; phosphorus compounds such as triphenyl phosphate (TPP), tricresyl phosphate (TCP), trixylyl phosphate (TXP), cresyl phenyl phosphate (CDP), tris(dichloropropyl) phosphate, tris(β-chloropropyl) phosphate, and tris(chloroethyl) phosphate; inorganic compounds such as magnesium hydroxide, aluminum hydroxide, diantimony trioxide, antimony pentoxide, molybdenum compounds, zinc nitrate, and zirconium oxide; nitrogen-containing compounds such as guanidine compounds, melamine compounds, and triazine compounds; and silicone compounds. Examples of the adhesive treatment include treatments with polyurethane resins such as ester-based urethane, ether-based urethane, carbonate-based urethane, prolactone-based urethane, and urethane-based elastomers; acrylic resins such as polyacrylates, polymethacrylates, and acrylic elastomers; vinyl chloride, vinyl chloride copolymers, and polyester-based resins.

[0027] The resin film constituting the laminate of the present invention preferably contains a thermoplastic resin, and the resin contained in the resin film is preferably made of a thermoplastic resin. Examples of thermoplastic resins include vinyl chloride; vinyl chloride copolymers; polyolefins such as polyethylene and polypropylene; ethylene-vinyl acetate copolymers; polyurethane resins such as ester-based urethane, ether-based urethane, carbonate-based urethane, prolactone-based urethane, and urethane-based elastomers; polyester-based resins such as unsaturated polyester resins and polyvinyl ester resins; acrylic resins such as polyacrylic esters, polymethacrylic esters, and acrylic elastomers; elastomers such as styrene-based elastomers, polyester-based elastomers, fluorine-based elastomers, and silicone-based elastomers. At least one of these may be included, and two or more of these may be used in combination. Among these, it is preferable to contain at least one selected from the group consisting of vinyl chloride, vinyl chloride copolymers, ethylene-vinyl acetate copolymers, polyurethane resins, polyester-based resins, and acrylic resins, and it is particularly preferable to contain vinyl chloride.

[0028] Vinyl chloride is usually used in combination with a plasticizer. Examples of the plasticizer include phthalate ester plasticizers such as dioctyl phthalate (DOP (DEHP)), diisononyl phthalate (DINP), diisodecyl phthalate (DIDP), dibutyl phthalate (DBP), dimethyl phthalate (DMP), diethyl phthalate (DEP), and benzyl butyl phthalate (BBP); adipate ester plasticizers such as dioctyl adipate (DOA (DEHA)) and isononyl adipate (DINA); sebacic acid ester plasticizers, trimellitic acid ester plasticizers such as trioctyl trimellitate (TOTM); pyromellitic acid ester plasticizers; polyester plasticizers; phosphate ester plasticizers such as tricresyl phosphate (TCP); citric acid plasticizers; ethylene-vinyl acetate ester copolymer polymer plasticizers; and ethylene-acrylic acid ester copolymer polymer plasticizers. When a plasticizer is contained, the content thereof is preferably 20 parts by mass to 80 parts by mass, and more preferably 40 parts by mass to 60 parts by mass, per 100 parts by mass of vinyl chloride.

[0029] The resin film may contain an ultraviolet absorbing agent, a colorant, a matting agent, a filler, and the like. Examples of the ultraviolet absorbing agent contained in the resin film include organic ultraviolet absorbing agents and inorganic ultraviolet absorbing agents. Examples of the organic ultraviolet absorbing agent include triazine compounds, cyanoacrylate compounds, benzophenone compounds, benzotriazole compounds, triazine compounds, and cyanoacrylate compounds. Examples of the inorganic ultraviolet absorbing agent include titanium oxide, zinc oxide, cerium oxide, and iron oxide. The ultraviolet absorbing agent may be used alone or in combination of two or more kinds. When the ultraviolet absorbing agent is contained, the content thereof is preferably 0.01% by mass to 5.00% by mass in the resin film, more preferably 0.10% by mass to 2.50% by mass, and even more preferably 0.20% by mass to 1.50% by mass.

[0030] Examples of colorants that may be contained in the resin film include pearl mica, mica coated with titanium oxide or iron oxide, aluminum powder, silver powder, gold powder, copper powder, bronze powder, powder of other metal alloys, metal-deposited flakes, and other metal or metal oxide-containing pigments, inorganic pigments other than metal or metal oxide-containing pigments, such as carbon, yellow lead, chrome vermilion, calcium carbonate, and baryte powder, and organic pigments such as permanent red, phthalocyanine green, and fast yellow. Preferably, a metal or metal oxide-containing pigment is used alone, or a mixture of a metal or metal oxide-containing pigment and an organic pigment and / or an inorganic pigment other than a metal or metal oxide-containing pigment is used. When a colorant is contained, the content of the colorant in the resin film is preferably 0.1% by mass to 50% by mass, more preferably 1% by mass to 30% by mass, and even more preferably 5% by mass to 20% by mass.

[0031] The thickness of the resin film is preferably 0.02 mm to 1.00 mm, more preferably 0.05 mm to 0.50 mm, and even more preferably 0.10 mm to 0.30 mm. When the thickness is equal to or greater than the lower limit, durability and design can be excellent, and when the thickness is equal to or less than the upper limit, processability and flexibility can be maintained and the obtained laminate can be made lighter.

[0032] The laminate of the present invention may further have a functional layer such as an antifouling layer, a coloring layer, a deodorant layer, or a heat-shielding layer in addition to the resin film and the fiber fabric. The resin film may also have the same function as that imparted by the functional layer. The functional layer may be disposed on one or both of the front and back surfaces of the laminate, or between the resin film layer and the fiber fabric. In particular, in the case of an antifouling layer, a deodorant layer, or a heat-shielding layer, it is preferable that the functional layer is disposed on one or both of the front and back surfaces of the laminate. When the laminate of the present invention has the functional layer in addition to the resin film, the thickness of the functional layer is preferably 1 μm or more, more preferably 5 μm or more, and preferably less than 20 μm.

[0033] Examples of the anti-smudge layer include a layer containing at least one resin selected from an acrylic resin, a fluorine-based copolymer resin, an acrylic-silicon copolymer resin, an acrylic-fluorine copolymer resin, an acrylic-urethane copolymer resin, and a blend of an acrylic resin and a fluorine-based copolymer resin, and at least one selected from silica fine particles, colloidal silica, an organosilicate, a silane coupling agent, an ultraviolet absorbing agent, and the like.

[0034] The deodorant layer may be made of a resin containing a deodorant. Examples of the deodorant include organic nitrogen compounds such as amines and hydrazines, organic deodorants such as metal chelate compounds, porous materials such as porous silica, silica gel, magnesium silicate, aluminum silicate, zeolite, sepiolite, activated carbon, and activated clay, and inorganic deodorants such as metal oxides such as alumina, zirconium oxide, zinc oxide, iron oxide, titanium dioxide, and zirconium phosphate. The content of the deodorant material is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more, and preferably 50 parts by mass or less, and more preferably 30 parts by mass or less, relative to 100 parts by mass of the resin constituting the deodorant layer. In addition, the resin constituting the deodorant layer may be the same as the resin constituting the resin film.

[0035] The coloring agent used in the colored layer may be the same as the coloring agent that may be contained in the resin film. The coloring agent contained in the colored layer is preferably 0.1% by mass to 50% by mass in the colored layer, more preferably 1% by mass to 30% by mass, and even more preferably 5% by mass to 20% by mass. The colored layer preferably contains a binder component from the viewpoint of adhesiveness. The binder component preferably contains at least one of polyurethane resins such as ester-based urethane, ether-based urethane, carbonate-based urethane, prolactone-based urethane, and urethane-based elastomers, polyester resins such as unsaturated polyester resins and polyvinyl ester resins, acrylic resins such as polyacrylic esters, polymethacrylic esters, and acrylic elastomers, vinyl chloride resins, vinyl chloride-vinyl acetate copolymer resins, ethylene-vinyl acetate copolymer resins, amide resins, and modified polyolefins. It is preferable to use the same type of resin as that contained in the resin film as the binder component used in the colored layer from the viewpoint of adhesiveness. The colored layer may be printed and does not necessarily have to be uniformly colored. It may have colored and non-colored areas, or it may have a plurality of colored areas of different colors.

[0036] The method for producing the laminate of the present invention is not particularly limited as long as it is a method for producing a laminate that satisfies the above-mentioned configuration. After preparing the fiber fabric and the resin film, they may be compression molded, or a resin film may be formed on at least one surface of the fiber fabric by a calendar method, a T-die extrusion method, a casting method, a dipping method, a coating method, or the like. If necessary, a functional layer may be provided on the fiber fabric or the resin film before or at the same time as integrating the fiber fabric and the resin film, or a functional layer may be provided after integrating the fiber fabric and the resin film. In addition, various functional layers can be formed by a calendar method, a T-die extrusion method, a casting method, a dipping method, a coating method, or the like, in the same manner as the resin film.

[0037] In the manufacturing process of the laminate of the present invention, the fiber woven fabric is preferably subjected to a heat setting process before being laminated with the resin film, and the temperature is preferably 100°C to 200°C, more preferably 140°C to 200°C, and even more preferably 160°C to 180°C. If this temperature is too high, not only will the tensile strength and tear strength decrease, but problems such as reduced flexibility will also occur. If the temperature is too low, problems such as shrinkage will occur when laminating with the resin film, which may lead to poor flatness. EXAMPLES

[0038] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these.

[0039] <Evaluation of shape forming ability> A 50 mm square sample was wrapped around an aluminum core with a diameter of 25 mm and a length of 170 mm and fixed with tape. The sample was placed in a 180°C oven and left for 30 minutes, then left at room temperature. If the sample had changed shape to match the aluminum core, it was judged by visual inspection as ◯, and if not, as ×.

[0040] <Tensile strength N / 30mm> The tensile strength (unit: N / 30mm) was measured at a pulling speed of 200mm / min according to the A method (strip method) specified in JIS L1096. A tensile strength of 500N / 30mm or more was judged to be good.

[0041] <Tear strength N> The tear strength (unit: N) was measured at a tensile speed of 200 mm / min according to the C method (trapezoid method) specified in JIS L1096. A tear strength of 50 N or more was judged to be good.

[0042] <Maintenance> 2mL of water was applied to a 100mm x 100mm sample, left for 10 minutes, and then lightly wiped with a dry towel to check for weight change and permeation of water to the back side. If the weight change rate ((weight before water application - weight after water application and wiping) / weight before water application x 100%) was less than 0.4% and the sample was moved to check for water droplets on the table on which the sample was placed, that is, visually checked for water permeation to the back side, it was judged to be good.

[0043] <Flexibility mm> The flexibility was evaluated using the JIS L1096:2010 bending resistance cantilever method (method A). Specifically, the sheets or laminates obtained in the examples and comparative examples were cut to 20 mm x 150 mm to prepare test pieces. The test pieces were placed on the horizontal part of a horizontal stand with one end inclined at 45°, and the end of the test piece far from the inclination was pressed with a metal plate and gently slid horizontally, so that the center of the tip of the test piece on the side not pressed with the metal plate sagged down, and the length of the tip of the side pressed with the metal plate when it came into contact with the inclined surface was read, and a length of 30 mm or more and 150 mm or less was judged to have good flexibility.

[0044] The materials constituting the laminate are as follows: <Textile fabric> Textiles and fabrics 1 Warp thread: core-sheath composite fiber Melset 280T48 (manufactured by Unitika Ltd., multifilament, 280dtex, core melting point 255℃, sheath melting point 165℃, core and sheath constituent resin: polyester resin) Weft: Core-sheath composite fiber Melset 280T48 Thread density: 48 x 48 threads per inch Heat set: 180℃ Textiles and fabrics 2 Warp thread: core-sheath composite fiber Melset 280T48 Weft: Polyester fiber (normal fiber, multifilament, 280dtex) Thread density: 48 x 48 threads per inch Heat set: 180℃ Textiles and fabrics 3 Warp thread: core-sheath composite fiber Melset 830T24 (manufactured by Unitika Ltd., multifilament, 830dtex, core melting point 255℃, sheath melting point 165℃, core and sheath constituent resin: polyester resin) Weft: Core-sheath composite fiber Melset 830T24 Thread density: 24 x 24 threads per inch Heat set: 140℃ Textiles and fabrics 4 Warp: Polyester fiber (normal fiber, multifilament, 830dtex) Weft: Polyester fiber (normal fiber, multifilament, 830dtex) Thread density: 27 x 27 threads per inch Textiles and fabrics 5 Warp thread: core-sheath composite fiber Melset 1680T24 (manufactured by Unitika Ltd., multifilament, 1680dtex, core melting point 255℃, sheath melting point 165℃, core and sheath constituent resin: polyester resin) Weft: core-sheath composite fiber Melset 1680T24 Thread density: 24 x 24 threads per inch Heat set: 140℃ Textiles and fabrics 6 Warp thread: core-sheath composite fiber Melset 1680T24 Weft: Polyester fiber (normal fiber, multifilament, 1680dtex) Thread density: 24 x 24 threads per inch Heat set: 140℃ Textiles and Fabrics 7 Warp thread: core-sheath composite fiber Melset 280T48 Weft: Core-sheath composite fiber Melset 280T48 Thread density: 12 x 12 threads per inch Heat Set: None <Resin film> Resin film 1 Material: Soft polyvinyl chloride resin Vinyl chloride resin: 48.2% by weight Phthalate ester plasticizer: 22.7% by weight Calcium carbonate: 14.5% by weight Ba-Zn stabilizer: 1.7% by weight Epoxidized soybean oil: 1.4% by weight Antimony trioxide: 4.3% by weight Titanium oxide: 6.8% by weight Organic additives: 0.4% by weight Thickness: 0.15mm Basis weight: 224g / m 2 Resin film 2 SB-5 (Tamapoly Co., Ltd.) Material: Ethylene-vinyl acetate copolymer VA rate 5% Thickness: 100μm Basis weight: 94g / m 2

[0045] <Example 1> Manufacturing method of laminate Two sheets of resin film 1 measuring 297 mm in length x 210 mm in width were prepared, and the resin film 1 was laminated on both sides of a fiber fabric 1 measuring 297 mm in length x 210 mm in width. The resin film 1 was then heat pressed for 30 seconds at a temperature of 150°C and a pressure of 3 MPa using a compression molding machine (for heating), and then cooled for 30 seconds using a compression molding machine (for cooling) to produce a laminate.

[0046] <Examples 2 to 4> A laminate was obtained under the same conditions as in Example 1, except that the fiber fabric and resin film were as shown in Table 1. The physical properties of the laminate are shown in Table 1.

[0047] <Comparative Example 1> Instead of the laminate, resin film 1 was used. The physical properties are shown in Table 2.

[0048] <Comparative Example 2> Instead of the laminate, resin film 2 was used. The physical properties are shown in Table 2.

[0049] <Comparative Example 3> Instead of the laminate, fiber fabric 1 was used. The physical properties are shown in Table 2.

[0050] <Comparative Example 4> Instead of the laminate, fiber fabric 2 was used. The physical properties are shown in Table 2.

[0051] <Comparative Example 5> Instead of the laminate, fiber fabric 3 was used. The physical properties are shown in Table 2.

[0052] <Comparative Example 6> Instead of the laminate, fiber fabric 4 was used. The physical properties are shown in Table 3.

[0053] <Comparative Examples 7 to 10> A laminate was produced in the same manner as in Example 1, except that the fiber woven fabric was as shown in Table 3. The physical properties and the like are shown in Table 3.

[0054] [Table 1]

[0055] [Table 2]

[0056] [Table 3]

[0057] The laminates of Examples 1 to 4, which satisfied the requirements of the present invention, had appropriate flexibility, and were excellent in shape formability, tensile properties, and elongation at break. They also had excellent maintainability. On the other hand, Comparative Examples 1 to 10 were insufficient in any one of shape forming ability, strength, maintainability, flexibility, and breaking elongation (an index of film sagging). [Industrial Applicability]

[0058] The laminate of the present invention is a flexible laminate, and when used for bags, there is no need to worry about the bag losing its shape even when the bag is thermally shaped into a predetermined shape, and the laminate has appropriate strength and flexibility and is easy to maintain. When used for roll blinds, the laminate has appropriate rigidity without using glass fibers, and can be used in bathrooms while preventing membrane sagging, and is therefore suitable for roll blinds and bags. [Explanation of symbols]

[0059] 1. Fabrics made from core-sheath composite fibers 2. Resin film

Claims

1. A laminate comprising at least one woven fiber fabric and at least one resin film; the resin film is disposed in an adhered state on at least one surface of the fiber woven fabric; The fiber woven fabric has a warp thread count of 20 threads / inch to 60 threads / inch, the fibers constituting the warp threads and the weft threads have a total fineness of 50 dtex to 950 dtex, the fibers constituting the fiber woven fabric contain 50 mass% or more of core-sheath composite fibers, the sheath of the core-sheath composite fibers has a melting point lower than that of the core, and the melting point of the sheath is 100°C to 180°C.

2. The laminate according to claim 1 , wherein 90% by mass or more of the fibers constituting the fiber woven fabric are organic fibers.

3. The laminate according to claim 1 , wherein the resin film contains a thermoplastic resin.

4. The laminate according to claim 3, wherein the thermoplastic resin constituting the resin film contains at least one selected from the group consisting of vinyl chloride, vinyl chloride copolymers, ethylene-vinyl acetate copolymers, polyurethane resins, polyester resins, and acrylic resins.

5. A laminate comprising at least one fiber woven fabric and at least one resin film, the resin film being arranged in a state of being adhered to at least one surface of the fiber woven fabric, the fiber woven fabric having a cover factor calculated by the following formula (I) in the range of 600 to 1900, and a basis weight of the fiber woven fabric of 250 g / m 2 The fibers constituting the fiber fabric contain 50 mass % or more of sheath-core composite fibers, the sheath of the core-sheath composite fibers has a melting point lower than that of the core, and the melting point of the sheath is 100°C to 180°C. Formula (I): Cover factor = (number of warp threads x √ warp thread fineness (dtex)) + (number of weft threads x √ weft thread fineness (dtex))

6. A laminate comprising at least one fiber woven fabric and at least one resin film, the resin film being bonded to at least one surface of the fiber woven fabric, and the fiber woven fabric having a basis weight of 50 g / m 2 ~250g / m 2 The fiber woven fabric has a thickness of 50 μm to 400 μm, the fibers constituting the fiber woven fabric contain 50 mass % or more of sheath-core composite fibers, and the sheath of the core-sheath composite fibers has a lower melting point than the core, and the melting point of the sheath is 100° C. to 180° C.

7. A roll curtain comprising the laminate according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Ekitainainozairyookongo oyobi bunrisurutamenokogyosochi

    JP1976065468A